The roles of heme oxygenase-1 in renal disease - Zhai, Hongfu; Ni, Lihua; Wu, Xiaoyan (Frontiers in Nephrology, 2023)
Heme oxygenase (HO), a heat shock protein containing hemoglobin, is an important enzyme in heme catabolism. It is involved in cell homeostasis and has anti-inflammatory, antioxidant, anti-apoptosis, immunomodulation, and other functions. It is expressed at a modest level in most normal tissues. When the body suffers from ischemia hypoxia, injury, toxins, and other nociceptive stimuli, the expression increases, which can transform the oxidative microenvironment into an antioxidant environment to promote tissue recovery from damage. In recent years, research has continued to verify its value in a variety of human bodily systems. It is also regarded as a key target for the treatment of numerous disorders. With the advancement of studies, its significance in renal disease has gained increasing attention. It is thought to have a significant protective function in preventing acute kidney injury and delaying the progression of chronic renal diseases. Its protective mechanisms include anti-inflammatory, antioxidant, cell cycle regulation, apoptosis inhibition, hemodynamic regulation, and other aspects, which have been demonstrated in diverse animal models. Furthermore, as a protective factor, its potential therapeutic efficacy in renal disease has recently become a hot area of research. Although a large number of preclinical trials have confirmed its therapeutic potential in reducing kidney injury, due to the problems and side effects of HO-1 induction therapy, its efficacy and safety in clinical application need to be further explored. In this review, we summarize the current state of research on the mechanism, location, and treatment of HO and its relationship with various renal diseases.